Performance of dye-sensitized solar cells with (PVDF-HFP)-KI-EC-PC electrolyte and different dye materials - Mohd Noor, Mazni; Buraidah, M.H.; Yusuf, S. N. F.; Careem, M. A.; Majid, S. R.; Arof, A.K. (Hindawi Publishing Corporation, 2011)
A plasticized polymer electrolyte system composed of PVDF-HFP, potassium iodide (KI), and equal weight of ethylene carbonate (EC) and propylene carbonate (PC) has been used in a dye-sensitized solar cell (DSSC). The electrolyte with the composition 40wt.